Preparation method and application of resin-based magnetic composite adsorption material

By using waste resin to prepare resin-based magnetic composite adsorption materials, the problems of poor adsorption selectivity and unstable treatment effect of existing adsorption materials are solved, and efficient adsorption and removal of a variety of heavy metal ions in wastewater are achieved, and the characteristics of multiple reuses are used.

CN116272908BActive Publication Date: 2025-03-04GUANGXI HUAXI GRP CO LTD

Patent Information

Application Number
CN202310367802.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-07
Publication Date
2025-03-04
Estimated Expiration
2043-04-07

AI Technical Summary

Technical Problem

The existing adsorbent materials have problems such as poor adsorption selectivity, unstable treatment effect, low adsorption capacity, frequent regeneration treatments, and high cost.

Method used

By using waste resin as a support, puffing and magnetic addition, combining the intercalation reaction of sodium phosphite and sodium hypophosphite, a resin-based magnetic composite adsorption material was prepared. This material can effectively adsorb and remove a variety of heavy metal ions in wastewater, and has the characteristics of multiple reuses.

Benefits of technology

It has achieved efficient adsorption and removal of various heavy metal ions such as cadmium, chromium, zinc, lead, manganese, and copper in wastewater. The materials can be reused many times. The preparation method is simple, the raw materials are cheap, and have high application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004167498360000041
    Figure BDA0004167498360000041
  • Figure BDA0004167498360000051
    Figure BDA0004167498360000051
  • Figure HDA0004167498370000011
    Figure HDA0004167498370000011
Patent Text Reader

Abstract

The present invention relates to the technical field of preparation of adsorbent materials for removing heavy metals from acidic wastewater, specifically a method for preparing a resin-based magnetic composite adsorbent material, comprising the following steps: using waste expanded resin as a base carrier, ferric chloride as an added magnetic auxiliary substance, mixing magnesium sulfate and aluminum sulfate evenly, stirring at high speed and ultrasonic dispersion, then adding sodium phosphite and sodium hypophosphite and placing them in a microwave reactor, adjusting the pH of the sodium phosphite and sodium hypophosphite in the reactor to precipitate, while the phosphite intercalates into the precipitate, finally filtering the precipitate and washing and drying to obtain a novel adsorbent material for excellent adsorption of heavy metals in acidic mine wastewater. The material prepared by the present invention can effectively adsorb various heavy metal ions such as cadmium, chromium, zinc, lead, manganese, copper, etc. in acidic mine wastewater, has a large adsorption capacity, and the adsorbent material has magnetism and can be regenerated by solid-liquid separation through magnetism.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of adsorbent materials for removing heavy metals from acidic wastewater, and specifically to a method for preparing and applying a resin-based magnetic composite adsorbent material. The resin-based magnetic composite adsorbent material is prepared by swelling waste resin and compounding with phosphite groups, and is used for removing cadmium, chromium, zinc, lead, manganese and copper from acidic wastewater. Background Art

[0002] Mining, electroplating, metal industry, battery manufacturing, smelting and other industries generate a large amount of wastewater containing heavy metal ions, such as lead, arsenic, copper, zinc, chromium, mercury, nickel, cadmium and manganese, during the production process. Heavy metal pollution in wastewater poses a huge threat to human health and environmental safety due to its high toxicity, bioaccumulation and non-biodegradability, and has attracted great public attention. If wastewater containing a variety of complex heavy metal ions and rare metal ions is directly discharged, it will inevitably cause pollution to the surrounding environment, endanger human health and ecological balance, and lose valuable metal resources. Therefore, in order to ensure global water security, it is crucial to effectively remove and recycle the toxic heavy metal pollutants that are widely present in wastewater resources.

[0003] In this regard, scholars have conducted a variety of studies on wastewater, mainly including natural degradation, microbial treatment, chemical precipitation, coagulation precipitation, adsorption, electrochemical deposition and a combination of multiple methods. Among them, natural degradation takes a long time and has poor results; microorganisms have a small specific surface area, surface active sites are often covered by organic matter, and the specific selection of metal ions is not strong. In practical applications, they are easily affected by external factors, so that they are greatly restricted in practical engineering applications; chemical precipitation and coagulation precipitation methods cannot effectively separate and recover metals and are easy to consume precipitants, which may introduce other metals; electrochemical deposition is time-consuming and cannot be carried out on a large scale in practical engineering applications; and adsorption has the advantages of a wide range of adaptability, fast processing speed, good effect, low cost, recyclable wastewater metal resources, and reusable adsorbents, and is widely used in wastewater treatment. The key to the successful application of adsorption is the selection of adsorbents. Selecting appropriate adsorbents according to actual conditions is of great significance for the economical treatment of wastewater containing heavy metal ions. Activated carbon is the earliest and most mature industrial adsorbent, but its high price, poor selectivity, high regeneration cost and difficulty in regeneration limit its application in some economically underdeveloped areas and low-profit industries. In the past decade, many scholars have explored cheap biomass adsorbents, mineral adsorbents, natural clay mineral adsorbents, organic composite adsorbents, resin-type leaching resins, impregnated resins, porous silicon-based adsorbents, etc. However, the existing adsorbent materials have problems such as poor adsorption selectivity, unstable treatment effect, low adsorption capacity, frequent regeneration leading to reduced service life, and high cost. Summary of the invention

[0004] In order to solve the problems of poor adsorption selectivity, unstable treatment effect, low adsorption capacity, frequent regeneration treatment leading to reduced service life and high cost in existing adsorption materials, the purpose of the present invention is to provide a method for preparing a resin-based magnetic composite adsorption material, using waste resin as a carrier material, through magnetization, aluminum sulfate and magnesium sulfate are added to produce precipitation, sodium phosphite and sodium hypophosphite are intercalated to introduce phosphorous acid groups, and an adsorption material that can effectively adsorb and remove cadmium, chromium, zinc, lead, manganese, copper and other heavy metal ions in wastewater is prepared, and anions can also be adsorbed. The composite functional adsorption material prepared by the method can be repeatedly recycled and reused, the preparation method is simple, the raw material price is low, and it has high application value.

[0005] The technical solution of the present invention is to provide a method for preparing a resin-based magnetic composite adsorption material, comprising the following steps:

[0006] (1) Preparation of carrier by expanding waste resin: waste ion exchange resin was used as raw material, washed 3 times with ethanol, washed 2 times with 1 mol / L hydrochloric acid, washed with water and dried, and the dried resin was expanded by airflow expansion, the airflow expansion pressure was 3 kPa, the resin water addition amount was 10%, and the expanded resin was used as carrier;

[0007] (2) Magnetic addition: prepare 100 ml of 1 mol / L ferric chloride solution, 0.3-0.8 mol / L magnesium sulfate solution, and 0.3-1 mol / L aluminum sulfate solution; put the carrier obtained in step (1) into the ferric chloride solution at a solid-liquid ratio of 1:2-1:5, then add the prepared magnesium sulfate solution and aluminum sulfate solution, and disperse by high-speed stirring and ultrasonic dispersion. The amount of magnesium sulfate and aluminum sulfate solution added is 20-50 ml;

[0008] (3) Adding phosphite groups: adding sodium phosphite and sodium hypophosphite to the mixed solution in step (2), wherein the amount of sodium phosphite added is 0.2-0.5 g and 0.1-0.3 g, respectively, and stirring at high speed for 2-5 min to obtain a mixed solution;

[0009] (4) Microwave pressure reaction: the mixed solution obtained in (3) is placed in a polytetrafluoroethylene pressure tank, and placed in a microwave digestion instrument for heating reaction. The microwave power is set to 500W to 1400W, the temperature is controlled to 120 to 170°C, the reaction time is 1 to 2 hours, and the mixture is moved to an oven for insulation for 8 to 12 hours, then cooled to room temperature, and filtered to obtain a precipitate;

[0010] (5) Precipitate cleaning and vacuum drying: The precipitate obtained in (4) is cleaned with deionized water and then placed in a vacuum drying oven for vacuum drying for 8 hours. After drying, the particles with a sieved particle size of 0.5 to 1 mm are the resin-based magnetic composite adsorption material.

[0011] Preferably, the magnetic addition in step (2) is to add the carrier obtained in step (1) into a ferric chloride solution at a solid-liquid ratio of 1:3, and then add 40 ml of a magnesium sulfate solution with a magnesium sulfate concentration of 0.5 mol / L and 30 ml of an aluminum sulfate solution with an aluminum sulfate concentration of 0.4 mol / L.

[0012] Preferably, in step (3), 0.3 g of sodium phosphite and 0.2 g of sodium hypophosphite are added, and stirring is performed for 3 min.

[0013] Preferably, in step (4), the microwave power is 1000 W, the temperature is controlled at 150° C., the reaction time is 2 h, and the oven is kept warm for 10 h.

[0014] The application of the resin-based magnetic composite adsorption material prepared by the method comprises the following steps:

[0015] (1) Heavy metal ion solution preparation: The concentration of each metal ion in the mixed solution of heavy metals cadmium, chromium, zinc, lead, manganese and copper is 0.5 to 100 mg / L; the solution pH is 2 to 8;

[0016] (2) Removal of heavy metal ions: the resin-based magnetic composite adsorption material is added to the heavy metal ion solution at a solid-liquid ratio of 1:5, and the air flow stirs the solution to adsorb and remove heavy metals;

[0017] The resin-based magnetic composite adsorption material is recovered and regenerated by removing the adsorbed material by using a magnet, and immersing the adsorbed material in a sodium hydroxide solution and a sodium phosphite and sodium hypophosphite solution for regeneration, wherein the sodium hydroxide concentration is 1 mol / L, the sodium phosphite solution concentration is 0.3-0.5 mol / L, and the sodium hypophosphite solution concentration is 0.3-0.5 mol / L.

[0018] The beneficial effects of the present invention are:

[0019] By making full use of waste resin as a base carrier and realizing the concept of treating waste with waste, it is creatively proposed to use waste resin for expansion as a carrier, and to use sodium phosphite and sodium hypophosphite for group addition to prepare a composite material with magnetic properties that can adsorb multiple heavy metal ions in the solution. The composite functional adsorption material prepared by this method can be recycled repeatedly, the preparation method is simple, the raw material price is low, and it has high application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The invention discloses a method for preparing the composite adsorption material and a flow chart for removing heavy metals from wastewater.

[0021] Figure 2 This is the effect of the expanded waste resin described in the present invention (Example 1).

[0022] Figure 3 This is the effect of the waste resin expanded according to the present invention (Example 2). DETAILED DESCRIPTION

[0023] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0024] Example 1

[0025] This embodiment is an example of a method for preparing the resin-based magnetic composite adsorption material of the present invention, comprising the following steps:

[0026] (1) Preparation of carrier by expanding waste resin: waste ion exchange resin is used as raw material, washed 3 times with ethanol, washed 2 times with 1 mol / L hydrochloric acid, washed with water and dried. The dried resin is expanded by airflow expansion, the airflow expansion pressure is 3 kpa, the resin water addition amount is 10%, and the expanded resin is used as a carrier, such as Figure 2 As shown, the resin produces a porous structure after expansion;

[0027] (2) Magnetic addition: Prepare 100 ml of 1 mol / L ferric chloride solution, 0.5 mol / L magnesium sulfate solution, and 0.4 mol / L aluminum sulfate solution; put the carrier obtained in step (1) into the ferric chloride solution at a solid-liquid ratio of 1:3, then add the prepared magnesium sulfate solution and aluminum sulfate solution, and disperse with high-speed stirring and ultrasonic dispersion. The magnesium sulfate concentration is 0.5 mol / L and the addition amount is 40 ml, and the aluminum sulfate concentration is 0.4 mol / L and the addition amount is 30 ml;

[0028] (3) Adding phosphite groups: adding sodium phosphite and sodium hypophosphite to the mixed solution in step (2), wherein the amounts of sodium phosphite added are 0.3 g and 0.2 g, respectively, and stirring at high speed for 3 min to obtain a mixed solution;

[0029] (4) Microwave pressure reaction: The mixed solution obtained in (3) was placed in a polytetrafluoroethylene pressure vessel and placed in a microwave digestion apparatus for heating reaction. The microwave power was set to 1000 W, the temperature was controlled to 150° C., the reaction time was 2 hours, and the mixture was moved to an oven for 10 hours of heat preservation, then cooled to room temperature, and filtered to obtain a precipitate.

[0030] (5) Precipitate cleaning and vacuum drying: The precipitate obtained in (4) is cleaned with deionized water, and then placed in a vacuum drying oven for vacuum drying for 8 hours. After drying, particles with a particle size of 0.5 to 1 mm are sieved to obtain the resin-based magnetic composite adsorption material.

[0031] (6) Heavy metal ion solution configuration: The concentration of each metal ion in the mixed solution of heavy metals such as cadmium, chromium, zinc, lead, manganese, copper, and nickel is 50 mg / L;

[0032] (7) Removal of heavy metal ions: The adsorbent material obtained in step (5) was put into the solution in (6), and different pH values ​​were set. The solid-liquid ratio was 1:5, i.e., 1 g of adsorbent material, 50 ml of solution, and the total amount of single element metal was 2.5 mg. The solution was stirred by airflow to produce adsorption. The temperature was 25 degrees at room temperature and the adsorption time was 2 hours. The adsorption removal rates of various metals in the heavy metal solution are shown in Table 1. Table 1 shows that the adsorption removal rates of cadmium, chromium, and lead metals in the solution by the adsorbent material were relatively large, followed by copper and nickel, and zinc and manganese were relatively weak.

[0033] (8) Adsorption material recovery and regeneration: The adsorption material after adsorption in (7) is removed by a magnet, and the adsorption material is regenerated by soaking in a sodium hydroxide solution and a sodium phosphite and sodium hypophosphite solution. The sodium hydroxide concentration is 1 mol / L, the sodium phosphite concentration is 0.5 mol / L, and the sodium hypophosphite concentration is 0.4 mol / L. After regeneration, the adsorption material still maintains a good adsorption effect on the heavy metal ions in the solution.

[0034] The saturated adsorption capacity of the prepared adsorption material is: cadmium 125.36 mg / g, chromium 113.97 mg / g, copper 98.24 mg / g, zinc 84.92 mg / g, manganese 85.32 mg / g, nickel 96.35 mg / g.

[0035] Table 1 Removal rate of metal ions in solution by adsorbent materials at a metal ion concentration of 50 mg

[0036]

[0037] It can be seen from the test results in Table 1 that as the pH of the solution increases, the removal rate of heavy metals in the solution by the adsorbent material prepared by the present invention gradually increases, especially for cadmium and chromium, it has very good adsorption and removal performance. When the pH of the solution is 4, the removal rate of cadmium and chromium by the adsorbent material reaches 99.26% and 95.37%, and the removal rate of nickel, copper and zinc reaches 68.32%, 55.73% and 41.57% at this time. It can be seen that the adsorbent material has good removal performance for heavy metal ions in the solution.

[0038] Example 2

[0039] This embodiment is another example of the method for preparing the resin-based magnetic composite adsorption material of the present invention, comprising the following steps:

[0040] (1) Preparation of carrier by expanding waste resin: waste ion exchange resin is used as raw material, washed 3 times with ethanol, washed 2 times with 1 mol / L hydrochloric acid, washed with water and dried. The dried resin is expanded by airflow expansion, the airflow expansion pressure is 3 kpa, the resin water addition amount is 10%, and the expanded resin is used as a carrier, such as Figure 3 As shown, the resin produces a porous structure after expansion.

[0041] (2) Magnetic addition: Prepare 100 ml of 1 mol / L ferric chloride solution, 0.4 mol / L magnesium sulfate solution, and 0.3 mol / L aluminum sulfate solution; put the carrier obtained in step (1) into the ferric chloride solution at a solid-liquid ratio of 1:3, then add the prepared magnesium sulfate solution and aluminum sulfate solution, and disperse with high-speed stirring and ultrasonic. The magnesium sulfate concentration is 0.4 mol / L and the addition amount is 30 ml, and the aluminum sulfate concentration is 0.3 mol / L and the addition amount is 20 ml.

[0042] (3) Adding phosphite groups: Add sodium phosphite and sodium hypophosphite to the mixed solution in step (2), with the amount of sodium phosphite added being 0.4 g and 0.3 g, respectively. Stir at high speed for 5 min to obtain a mixed solution.

[0043] (4) Microwave pressure reaction: The mixed solution obtained in (3) was placed in a polytetrafluoroethylene pressure tank and placed in a microwave digestion apparatus for heating reaction. The microwave power was set to 1200 W, the temperature was controlled to 160° C., the reaction time was 1.5 hours, and the mixture was moved to an oven for insulation for 8 hours, then cooled to room temperature and filtered to obtain a precipitate.

[0044] (5) Precipitate cleaning and vacuum drying: The precipitate obtained in (4) is cleaned with deionized water, and then placed in a vacuum drying oven for vacuum drying for 8 hours. After drying, particles with a particle size of 0.5 to 1 mm are sieved to obtain the resin-based magnetic composite adsorption material.

[0045] (6) Heavy metal ion solution configuration: The concentration of each metal ion in the mixed solution of heavy metals such as cadmium, chromium, zinc, lead, manganese, copper, and nickel is 20 mg / L;

[0046] (7) Removal of heavy metal ions: The adsorbent material obtained in step (5) was put into the solution in (6), and different pH values ​​were set. The solid-liquid ratio was 1:3, i.e., 2 g of adsorbent material, 60 ml of solution, and the total amount of single element metal was 1.2 mg. The solution was stirred by airflow to produce adsorption. The temperature was room temperature at 25 degrees and the adsorption time was 2 hours. The adsorption removal rates of various metals in the heavy metal solution are shown in Table 1. Table 1 shows that the adsorption removal rate of the adsorbent material in the solution is almost 100%, and it can highly adsorb and remove heavy metal ions in the solution.

[0047] (8) Adsorption material recovery and regeneration: The adsorption material after adsorption in (7) is removed by a magnet, and the adsorption material is regenerated by soaking in a sodium hydroxide solution and a sodium phosphite and sodium hypophosphite solution. The sodium hydroxide concentration is 1 mol / L, the sodium phosphite concentration is 0.5 mol / L, and the sodium hypophosphite concentration is 0.4 mol / L. After regeneration, the adsorption material still maintains a good adsorption effect on the heavy metal ions in the solution.

[0048] Table 2 Removal rate of metal ions in solution by adsorbent materials when the metal ion concentration is 20 mg

[0049]

[0050] From the test results in Table 2, it can be seen that as the pH of the solution increases, the removal rate of heavy metals in the solution by the adsorbent prepared by the present invention increases accordingly, and the adsorbent can simultaneously remove multiple heavy metal ions in the solution. When the pH of the solution is 4, the removal rate of cadmium, chromium, copper, zinc, and nickel by the adsorbent is more than 90%, and the removal rate of manganese is also 87.01%. It can be seen that the adsorbent has good performance in removing heavy metal ions in the solution.

Claims

1. A method for preparing a resin-based magnetic composite adsorption material, characterized in that: The steps include: (1) Preparation of carrier by expanding waste resin: waste ion exchange resin was used as raw material, washed 3 times with ethanol, then washed 2 times with 1 mol / L hydrochloric acid, finally washed with water and dried, and the dried resin was expanded by airflow expansion, the airflow expansion pressure was 3 kpa, the resin water addition amount was 10%, and the expanded resin was used as a carrier; (2) Magnetic addition: prepare 100 ml of 1 mol / L ferric chloride solution, 0.3-0.8 mol / L magnesium sulfate solution, and 0.3-1 mol / L aluminum sulfate solution; put the carrier obtained in step (1) into the ferric chloride solution at a solid-liquid ratio of 1:2-1:5, then add the prepared magnesium sulfate solution and aluminum sulfate solution, and disperse by high-speed stirring and ultrasonic dispersion. The amount of magnesium sulfate and aluminum sulfate solution added is 20-50 ml; (3) Adding phosphite groups: adding sodium phosphite and sodium hypophosphite to the mixed solution in step (2), wherein the amount of sodium phosphite added is 0.3 g and the amount of sodium hypophosphite added is 0.2 g, and stirring is performed for 3 min to obtain a mixed solution; (4) Microwave pressure reaction: the mixed solution obtained in step (3) is placed in a polytetrafluoroethylene pressure tank, and placed in a microwave digestion instrument for heating reaction. The microwave power is set to 500W~1400W, the temperature is controlled to 120~170°C, the reaction time is 1~2 hours, and the mixture is moved to an oven for insulation for 8~12 hours, then cooled to room temperature, and filtered to obtain a precipitate; (5) Precipitate cleaning and vacuum drying: The precipitate obtained in step (4) is cleaned with deionized water, and then placed in a vacuum drying oven for vacuum drying for 8 hours. After drying, particles with a particle size of 0.5 to 1 mm are sieved to obtain the resin-based magnetic composite adsorption material.

2. The method for preparing a resin-based magnetic composite adsorption material according to claim 1, characterized in that: The magnetic addition in step (2) is to add the carrier obtained in step (1) into a ferric chloride solution at a solid-liquid ratio of 1:3, and then add 40 ml of a magnesium sulfate solution with a magnesium sulfate concentration of 0.5 mol / L and 30 ml of an aluminum sulfate solution with an aluminum sulfate concentration of 0.4 mol / L.

3. The method for preparing a resin-based magnetic composite adsorption material according to claim 1, characterized in that: In step (4), the microwave power is 1000 W, the temperature is controlled at 150° C., the reaction time is 2 h, and the oven is kept warm for 10 h.

4. Application of the resin-based magnetic composite adsorption material prepared by the method of claim 1, characterized in that: The steps include: (1) Heavy metal ion solution preparation: The concentration of each metal ion in the mixed solution of heavy metals cadmium, chromium, zinc, lead, manganese and copper is 0.5~100 mg / L; the solution pH is 2~8; (2) Removal of heavy metal ions: The resin-based magnetic composite adsorption material is added to the heavy metal ion solution at a solid-liquid ratio of 1:5, and the air flow stirs the solution to produce adsorption and remove heavy metals.

5. The use according to claim 4, characterized in that: The adsorbent material after adsorption is removed by a magnet, and the adsorbent material is immersed in a sodium hydroxide solution and a sodium phosphite and sodium hypophosphite solution for regeneration, wherein the sodium hydroxide concentration is 1 mol / L, the sodium phosphite solution concentration is 0.3-0.5 mol / L, and the sodium hypophosphite solution concentration is 0.3-0.5 mol / L.

Citation Information

Patent Citations

  • Preparation method of nanometer adsorbent for removing heavy metals contained in wastewater

    CN103301819A

  • Deep treatment method for removing cyanogen and chromium synchronously in electroplating sewage

    CN106116042A

Cited By

  • Novel resin-based filtering material as well as preparation method and application thereof

    CN119912024A

  • A resin-based filter material, its preparation method and application

    CN119912024B